Pemberian Mulsa dan Penguat Teras Pada Tiga Jenis Tanaman Terhadap Limpasan Permukaan, Erosi, Pertumbuhan dan Hasil Tanaman Pada Tanah Andisol - Jaka Suyana; Sumarno Sumarno; Supriyono Supriyono; Nanik Puji Lestariningsih (Agrosains : Jurnal Penelitian Agronomi, 2017)
Erosion is the main factor causing  land degradation in area of planting vegetables dominated by Andisol soil. Andisol soil contains more fraction of dust so it is easily transported by runoff. This study aim to determine the influence of mulching corn stem with a terrace strengthen (Vetiveria zizanioides, Coix  lacryma-jobi  L., Panicum muticum, Annona squamosa) to surface runoff, erosion, growth and result of plant (red lentils, cabbage and white lentils) in Andisol soil. This study uses a randomized complete block design with four (4) treatment and repeated three (3) times as a group so that there are twelve (12) experimental unit. The grouping based on kinds of plant that are cabbage, red lentils and white lentils. The results showed that MS4 treatment (mulch corn stem twelve (12) ton/ha with panicum muticum+ Annona squamosa as terrace strengthen) produces smallest of surface run off, erosion and dry weight of weeds, increased growth and canopy and increased crop yields 40.27% of red lentils, 57.10% of cabbage and 14.54% of white lentils.